Measuring vulnerability of marine and coastal habitats' potential to deliver ecosystem services - Willaert, Tom (2019)
This study was supported by the Calouste Gulbenkian Foundation, Portugal, through the research project MCES-The Economic Valuation and Governance of Marine and Coastal Ecosystem Services, in the context of the Gulbenkian Oceans' Initiative. We also thank to FCT/MEC due to the financial support to CESAM, through national funds (UID/AMB/50017/2019) and the co-funding by the FEDER, within the PT2020 Partnership Agreement and Compete 2020 (UID/AMB/50017/2013).